"My job is to unsettle folks": Perspectives on a praxis toward racial justice. (June 2021) - Moore, Ashley E.
Abstract: Using phenomenographic case study, this article explores antiracist teacher education praxis through the perspectives of student-nominated faculty. I theorize four concrete practices that serve to move teacher education pedagogy closer to active antiracism: 1) model vulnerability; 2) shift agency; 3) build community; and 4) pose questions. These practices are further explicated and understood as existing at the root of humanization and criticality. I ultimately argue that teacher education must be a project in humanization in order to be truly antiracist, and that teacher preparation programs must be grounded in critical race theories. Implications for future research are also discussed. Highlights: Student-nominated faculty described their antiracist praxis. Praxis described: model vulnerability, shift agency, build community, ask questions. Antiracist teacher education is both humanizing and critical. Teacher preparation programs must be humanizing and include critical race theories.